Effects of meso-M(PPh3)2Cl (M = Pd, Ni) substituents on the linear and third-order nonlinear optical properties of chalcogenopyrylium-terminated heptamethines in solution and solid states12. Issue 14 (15th December 2017) - Davydenko, Iryna; Benis, Sepehr; Shiring, Stephen B.; Simon, Janos; Sharma, Rajesh; Allen, Taylor G.; Chi, San-Hui; Zhang, Qing; Getmanenko, Yulia A.; Parker, Timothy C.; Perry, Joseph W.; Brédas, Jean-Luc; et al.
Abstract : Pd(PPh3 )2 Cl groups hinder aggregation and afford promising solid-state NLO properties. Abstract : Aggregation of cyanine-like dyes can significantly affect their optical properties. Here we report the effects of bulky meso -M(PPh3 )2 Cl (M = Pd, Ni) substitution on the molecular and solid-state optical characteristics of chalcogenopyrylium-terminated heptamethines. Metallated dyes were synthesised by reaction of the meso -chloro dyes with Pd(PPh3 )4 or Ni(PPh3 )4 at room temperature. The two PPh3 ligands are trans and the plane formed by the metal atom and its ligands is approximately orthogonal to that of the polymethine π-system. Replacement of Cl by M(PPh3 )2 Cl leads to a large blue shift of the solution absorption maximum and a decrease in the associated transition dipole moment, these effects being slightly more pronounced for Ni than for Pd. DFT calculations and electrochemical data suggest the blue shifts can largely be attributed to destabilisation of the LUMO by the more strongly π-donating M(PPh3 )2 Cl groups. The magnitude of the real part of the molecular third-order polarisability, Re( γ ), decreases in the order Cl > Pd(PPh3 )2 Cl ≫ Ni(PPh3 )2 Cl. Within the framework of the sum-over-states expression for Re( γ ), the difference between Cl and Pd(PPh3 )2 Cl examples can be rationalised considering the effects of the S0 → S1 transition energy and transition dipole moment on the two-state term associated with S0 → S1 . On the other hand, the magnitude of Re( γ ) for a Ni(PPh3 )2 Cl dye is anomalously low; SAC-CI/HF/cc-pVDZ excited-state calculations reveal this is due to a two-photon-allowed S2 state at unusually low energy for a cyanine-like dye, leading to a large positive three-state contribution to γ opposing the negative two-state S1 term. Thus, despite a cyanine-like molecular structure and linear absorption spectrum, this compound does not exhibit cyanine-like nonlinear optical behavior. Turning to the effects on aggregation, molecular dynamics simulations suggest that Pd(PPh3 )2 Cl substitution largely suppresses H- and J-aggregate formation; indeed experimental absorption spectra for neat films of Pd(PPh3 )2 Cl-substituted dyes are fairly similar to corresponding solution spectra. A 50 wt% blend of a Pd(PPh3 )2 Cl-substituted telluropyrylium-terminated dye with amorphous polycarbonate exhibits a third-order susceptibility of −3 × 10 −11 esu, a two-photon figure-of-merit in excess of 10, and linear loss of 6.3 dB cm −1, which are close to the requirements for all-optical switching applications.